Strength and power determinates of rowing performance - Chun-Jung, H.; Nesser, T. W.; Edwards, J. E. (Journal of Exercise Physiology online, 2007)
Rowing is an activity that involves both the upper and lower body, making it a total body exercise. The purpose of this study was to determine which physiological variables account for the most variation in 2000m rowing performance. Ten male (age = 17.4 ± 0.7 yr, weight = 75.2 ± 11.2 kg, height = 181.4 ± 6.1 cm) and seven female rowers (age = 17.3 ± 0.6 yr, weight = 72.4 ± 14.9 kg, and height = 168.3 ± 6.7 cm) participated in this study. Performance variables tested include a 2000m rowing ergometer time trial (8.01 ± 0.69 min), vertical jump (42.6 ± 10.7 cm), inverted row (9.8 ± 6.3 rep), leg press (144.7 ± 25.4 kg), and back extension (26.3 ± 11.1 rep). Significant correlations (p = 0.05) with 2000m rowing performance were identified for vertical jump (r = -0.736), inverted row (r = -0.624), leg press (r = -0.536), and height (r = -0.837). A stepwise multiple regression analysis identified height and leg press as the strongest predictors of 2000m rowing performance (R2= 0.807, p = 0.05). With height removed as an independent variable, a stepwise multiple regression was run again, identifying vertical jump, weight, and age as the best predictors of 2000m rowing performance (R2= 0.842, p = 0.05). Height and leg press were identified as the strongest predictors of 2000m rowing performance. With height removed as an independent variable vertical jump, weight, and age best predicted 2000m rowing performance. Inverted row, despite its strong correlation, did not further contribute to either prediction equation. The results of this study support the importance of strength and anaerobic power development in male and female club level rowers. ABSTRACT FROM AUTHOR